ASPEK HUKUM PRINSIP TATA KELOLA PERUSAHAAN YANG BAIK DAN PENERAPANNYA PADA BADAN USAHA MILIK DESA - Maria Fransiska Owa da Santo; Yustinus Pedo (SASI, 2020)
Villages in the era of regional autonomy have the authority to determine the direction of development by optimizing the management of village funds through the establishment and development of Village-Owned Enterprises (BUMDES). This study aims at the concern of villages in NTT Province that have not made BUMDES as a vehicle for managing the Village Fund and as a comparison for researchers who took the research location in Kokbaun District, TTS Regency, NTT Province. This research is a descriptive legal research with the type of research is normative-empirical legal research. This type of research requires secondary data and primary data. The research data shows that the Village Government in Kokbaun District has understood the importance of establishing BUMDES as mandated by the Village Law, but there are obstacles in the implementation of its formation and development. The obstacles are the quality of Human Resources, namely the lack of understanding of villagers and the lack of skilled personnel in managing BUMDES in accordance with the articles of association and bylaws and understanding of village development. The principles of good corporate governance can help BUMDES management so that it becomes more focused and ultimately can increase village income which will also affect the development and economic development of rural communities.